Evaluation of Medication Error Reports Sent to Food and Drug Deputy From Hospitals Affiliated to Mazandaran University of Medical Sciences, Mazandaran Province, Iran, 2015-2018 - Mohammad Eslami Jouybari; Fatemeh Izadpanah; Mina Amini (Mazandaran University of Medical Sciences, 2020)
Background: Medical errors are one of the most common threats to patient safety. Medication errors have several consequences, including the increase in patients' mortality, length of stay, and healthcare costs. Objectives: This study was conducted in Food and Drug Deputy of Mazandaran University of Medical Sciences (MAZUMS) to evaluate medication errors. Methods: This study was conducted by the Food and Drug Deputy of Mazandaran University on medication errors reported and received from affiliated hospitals during 2015-2018. The analysis was performed based on the cause of the error, the frequency of the drugs, routs of administration, and the type. Results: Out of 3033 reported cases, the results of data analysis indicated that the highest percentage of these errors was related to antibiotics (22.84%). According to the results, the most common type of error belonged to the incorrect drug (44.18%), incorrect dose (25.65%), and drug omission (16.68%). The most common cause of the errors was related to neglect and insufficient care by the medical team (38.24%) and no or incorrect mention of the details of prescribed medications (in Kardex, HIS, etc.) by nurses (14.96%). Conclusion: Regular in-hospital training for medical staff focused on teaching the standards required for the administration and use of various medications, and identification of common medication errors can prepare guidelines to reduce these errors in hospitals. Besides, providing measures such as electronic prescription and medication systems based on a unit-dose drug distribution system can also help reduce medication errors.